2018
DOI: 10.1002/dc.24122
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic clues indicating tall cell variants of papillary thyroid carcinoma in fine needle aspiration

Abstract: Background The definition of tall cell variant of papillary thyroid carcinoma (TCV‐PTC) depends on the articles, and the defined cytological findings characteristic of TCV‐PTC have not yet been fully analyzed. This study aimed to establish the cytological characteristics of TCV‐PTC. Methods We retrospectively analyzed the smears of 19 TCV‐PTC and 50 conventional PTC (C‐PTC) cases. Results Palisaded pattern with the nuclei locating at the base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Key point: Chest CT is not indicated at initiation of AS but may be indicated if there is disease progression. 20.9% in the 40s, 10.3% in the 50s, 8.2% in the 60s, and 3.5% in the 70s (34). Other studies have also demonstrated a lower rate of PTMC progression in older patients (15)(16)(17)35).…”
Section: Evaluation Of Distant Metastasis With Chest Ctmentioning
confidence: 90%
See 1 more Smart Citation
“…Key point: Chest CT is not indicated at initiation of AS but may be indicated if there is disease progression. 20.9% in the 40s, 10.3% in the 50s, 8.2% in the 60s, and 3.5% in the 70s (34). Other studies have also demonstrated a lower rate of PTMC progression in older patients (15)(16)(17)35).…”
Section: Evaluation Of Distant Metastasis With Chest Ctmentioning
confidence: 90%
“…In addition, FNAC features suggestive of aggressive subtypes of PTC, such as tall cell variant, are recommended for immediate surgery, although direct evidence for this is lacking, and suspicion of such subtypes based on FNAC alone is not easy to diagnose in practice (20,21). Kuo et al investigated surgical cases of 18,260 conventional PTMCs and found 97 tall cell variant of PTMCs, and 90 diffuse sclerosing variant of PTMCs (22).…”
Section: Diagnosis and Decision-makingmentioning
confidence: 99%
“…Aggressive cytologic or histopathologic tumor characteristics have been demonstrated as contraindications to AS in previous studies [ 7 , 12 , 15 ]. Even though Tanaka et al [ 34 ] suggested five cytological findings indicating the tall-cell variant of PTC, the cytohistological findings might be different from final histologic findings because the proportion of tall columnar cells in the final histology is important for diagnosing the tall-cell variant of PTC. Furthermore, the cytohistological findings of other aggressive variants are not known.…”
Section: Optimal Indications For Asmentioning
confidence: 99%
“…Classically for these tumors that are considered as "intermediate risk" according to the ATA, the option of a total thyroidectomy is generally retained. [29][30][31] In particular, the tall-cell variant of PTC is more likely to present with multifocal and bilateral disease, thus the indication becomes more compelling under such circumstances. 32 The removal of all thyroid tissue is justified for most tall-cell and other aggressive variants based on a higher likelihood for ETE.…”
Section: Tumor Characteristicsmentioning
confidence: 99%
“…However, such variants are more often diagnosed on histopathology. Classically for these tumors that are considered as “intermediate risk” according to the ATA, the option of a total thyroidectomy is generally retained 29‐31 . In particular, the tall‐cell variant of PTC is more likely to present with multifocal and bilateral disease, thus the indication becomes more compelling under such circumstances 32 .…”
Section: Decision‐making Process In the Staged Thyroidectomy Approachmentioning
confidence: 99%